Pemanfaatan Alat Termometer Otomatis dalam Meningkatkan Pelayanan di Posyandu Desa Pulogedang - Rina Dian Rahmawati; Muhammad Wahyudi; Siti Nafisatul Azizah Qumairoh; Siti Mukhlishotul Muhimmah; Kholishotul Amaliyah (Faculty of Tarbiyah and Teacher Training, 2023)
By looking at the current development of technology, it is necessary to carry out reforms in various scientific fields ranging from economics, education to the health sector. But what is happening in society, the latest technology is not really sufficient either in terms of manufacture or utilization. The objectives of the community service program that is being carried out include: 1) the community is well acquainted with the results of the latest technology. 2) people are able to understand more deeply related to today's technology. To achieve this goal, several activities were carried out, such as: 1) Participating in supporting activities related to health program partners, namely posyandu officers, cadres and local midwives, 2) Conducting seminars. The results of this activity are in the form of understanding and utilization in the form of a thermometer tool. The tool was measured using a questionnaire and yielded a value of 90%, so it can be concluded that in the program of activities this community group is interested in developing an automatic thermometer tool.